Advances in flowering phenology across the Northern Hemisphere are explained by functional traits. Issue 3 (27th December 2017) - König, Patrizia; Tautenhahn, Susanne; Cornelissen, J. Hans C.; Kattge, Jens; Bönisch, Gerhard; Römermann, Christine
Abstract: Aim: Numerous studies have reported changes in first flowering day (FFD‐changes) in response to changes in climate. However, regarding the direction (advances versus delays) and the intensity (number of days/decade) of FFD‐changes, species show differences even when observed in the same location. Here, we examine the extent to which plant traits can explain observed differences in the response of flowering phenology in trees, shrubs, herbs and grasses. Location: Eighteen sites distributed over the Northern Hemisphere. Methods: We compiled data from the literature on FFD‐changes over recent decades for 562 species (648 observations). We related FFD‐changes to predictor variables associated with (a) changes in climate, (b) local site conditions and (c) traits. Results: Of all FDD‐changes, 80.4% were FFD‐advances, 69.9% not exceeding 5 days/decade, and 10.5% exceeding 5 days/decade, whereas 19.6% reported delays. The intensity of FFD‐advances could be explained by several predictor variables from all three groups (a–c). The importance of these variables differed between the growth forms. Overall, decreasing precipitation was more important than increasing temperature in explaining FFD‐advances. FFD‐advances were strongest in polar tundra and in dry and warm habitats. Traits related to competition and growth rate, like plant height, specific leaf area and leaf dry matter content, had substantial explanatory power in the models. Traits had the highest overall importance in trees and grasses. In herbs they were of equal importance with changes in climate. In shrubs, variables related to site conditions best explained the intensity of FFD‐advances. Main conclusions: Plant traits are important to understand species‐specific and growth form‐specific differences in phenological responses to climatic changes. Hence, in future observations and predictions of plant phenology, traits should be taken into consideration, especially those related to competition and growth rate, as they improve our understanding of adaptations leading to phenological changes.